Network location and learning: the influence of network resources and firm capabilities on alliance formation - Gulati, Ranjay (Strategic Management Journal, 1999)
This paper presents a dynamic, firm-level study of the role of network resources in determining alliance formation. Such resources inhere not so much within the firm but reside in the interfirm networks in which firms are placed. Data from extensive fieldwork show that by influencing the extent to which firms have access to information about potential partners, such resources are an important catalyst for new alliances, especially because alliances entail considerable hazards. This study also assesses the importance of firms’ capabilities with alliance formation and material resources as determinants of their alliance decisions. I test this dynamic framework and its hypotheses about the role of time-varying network resources and firm capabilities with comprehensive longitudinal multi-industry data on the formation of strategic alliances by a panel of firms between 1970 and 1989. The results confirm field observations that accumulated network resources arising from firm participation in the network of accumulated prior alliances are influential in firms’ decisions to enter into new alliances. This study highlights the importance of network resources that firms derive from their embeddedness in networks for explaining their strategic behavior. Copyright © 1999 John Wiley & Sons, Ltd.